Systematic review with meta‐analysis: prevalence, risk factors and costs of aminosalicylate use in Crohn's disease. Issue 2 (30th May 2018) - Ma, C.; Dutton, S. J.; Cipriano, L. E.; Singh, S.; Parker, C. E.; Nguyen, T. M.; Guizzetti, L.; Gregor, J. C.; Chande, N.; Hindryckx, P.; Feagan, B. G.; Jairath, V.
Summary: Background: Aminosalicylates are the most frequently prescribed drugs for patients with Crohn's disease (CD), yet evidence to support their efficacy as induction or maintenance therapy is controversial. Aims: To quantify aminosalicylate use in CD clinical trials, identify factors associated with use and estimate direct annual treatment costs of therapy. Methods: MEDLINE, Embase and CENTRAL were searched to April 2017 for placebo‐controlled trials in adults with CD treated with corticosteroids, immunosuppressants or biologics. The proportion of patients co‐prescribed aminosalicylates in placebo arms was pooled using a random‐effects model. Meta‐regression was used to identify factors associated with aminosalicylate use. Annual treatment costs were estimated using the 2016 Ontario Drug Benefit Program. Results: Forty‐two induction and 10 maintenance trials were included. The pooled proportion of patients co‐prescribed aminosalicylates was 44% [95% CI: 39%‐49%] in induction trials and 49% [95% CI: 35%‐64%] in maintenance trials. There was substantial to considerable heterogeneity ( I 2 = 86.0%, 91.8% for induction and maintenance trials, respectively). In multivariable meta‐regression, aminosalicylate use has decreased over time in induction trials (OR 0.50 [95% CI: 0.34–0.74] per 10‐year increment). While a decline has been seen over time, 35% of CD patients were still using aminosalicylates in contemporary trials from the last 5 years. The estimated annual cost for the lowest price mesalazine (mesalamine) formulation is approximately 32 million for the Canadian CD population. Conclusions: Over one‐third of CD patients entering clinical trials are still co‐prescribed aminosalicylates. A definitive trial is needed to inform the conventional practice of using aminosalicylates as CD maintenance therapy. Abstract : Linked Content This article is linked to Mansfield and MacDougall and Jairath et al papers. To view these articles visithttps://doi.org/10.1111/apt.14859 andhttps://doi.org/10.1111/apt.14908 .